Transformative learning: reflection on the emotional experiences of schoolteachers during and after the pandemic - Chiu, Yin Yung (Frontiers in Education, 2025)
Teachers have experienced online teaching anxiety since the pandemic, and as education continues with digitization, the emotional experiences should be addressed. By focusing on the emotions experienced by schoolteachers in online teaching, this research investigates how intense feelings, and strong emotions can be transformed into critical self-reflection and ultimately achieve transformation based on the transformative learning model. As teachers across jurisdictions reportedly experienced burnout, this research discovers that transformative learning is the gateway and a path that allows teachers' passion to be reignited. To cope with the changes and challenges brought by the use of AI and the vastness of online information, it is essential for teachers to re-examine and identify their roles in the classroom and to consolidate their valuable contributions and irreplaceable role in an effective learning environment. Through case studies that cover the life stories of five teachers in Hong Kong, Canada and Taiwan, this research discusses how the emotionality of teachers plays a key role in transformative learning and examines the process in which anxieties transcend into passion.